Project management best practices : achieving global excellence - Kerzner, Harold (Wiley, 2018)
"Implement Best Practices to Achieve Project Management Excellence The quintessential guide to managing projects, Project Management Best Practices, features comprehensive coverage of the topics of planning, scheduling, controlling, and measuring value within the project management context. With input from senior executives and project managers from over 50 world-class companies, this complete resource is truly the project manager’s bible. Author Harold Kerzner provides rare insight into a topic with ever more far-reaching implications for competitive businesses. For middle- and senior-level managers, this compendium of insight from companies like Airbus, Heineken, Dell, IBM, Boeing, and many more will help with implementing the type of project management best practices that add value and efficiency to every level of an organization. The book: Includes the most up-to-date project management best practices Offers new material on the important topics of agile and Scrum Features insights from world-class organizations from Sony to Cisco Also includes instructor resources and handy PowerPoint guides Project Management Best Practices is the perfect resource for upper-level undergraduate and graduate-level courses, as well as an excellence reference for seasoned professionals"-- Provided by publisher